2015
DOI: 10.2208/jscejhe.71.i_457
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Radar Rainfall Accuracy of Xrain by Modifying of Rainfall Attenuation Correction and Compositing Radar Rainfall

Abstract: 正会員 博(工) 国土交通省 国土技術政策総合研究所 河川研究部(〒305-0804 茨城県つくば市旭1)2 正会員 修(工) 国土交通省 国土技術政策総合研究所 河川研究部(〒305-0804 茨城県つくば市旭1)The Ministry of Land, Infrastructure, Transport and Tourism (MLIT) built the rainfall observation network composed of 38 X-band dual polarimetric radars called XRAIN. The results of verifying the accuracy of the XRAIN rainfall, attenuation correction caused underestimation of radar rainfall distant from radar, and that underestimation caused underestimation of the compositing rainfall close to radar. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The XRAIN rainfall rate was used as the input for the rainfall-rate nowcast model. Although the accuracy of XRAIN has been assessed by numerous previous studies, such as Tsuchiya et al (2015) and Kim and Maki (2012), strictly speaking, the rainfall observed by XRAIN was not equal to the rain gauge observations because the targets were observed at different heights in each case. Our results focus on the difference between radar observations and predictions, whereas ground truth verification is not considered because CASE1 and CASE2 were too small to be accurately detected by AMeDAS.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The XRAIN rainfall rate was used as the input for the rainfall-rate nowcast model. Although the accuracy of XRAIN has been assessed by numerous previous studies, such as Tsuchiya et al (2015) and Kim and Maki (2012), strictly speaking, the rainfall observed by XRAIN was not equal to the rain gauge observations because the targets were observed at different heights in each case. Our results focus on the difference between radar observations and predictions, whereas ground truth verification is not considered because CASE1 and CASE2 were too small to be accurately detected by AMeDAS.…”
Section: Resultsmentioning
confidence: 97%
“…Then, the rainfall intensities from all radars belonging to the same intensive observation area are interpolated onto a horizontal grid with a grid spacing of 11.25″ in longitude and 7.5″ in latitude (a spatial resolution of approximately 250 m). All polar coordinate grid points under 5,000 m were taken into consideration using the weighted Cressman interpolation method when generating the XRAIN composite rainfall map (Tsuchiya et al 2015). The data were provided by the National Institute for Land and Infrastructure Manage-ment (NILIM).…”
Section: Two-and Three-dimensional Radar Datamentioning
confidence: 99%
“…The XRAIN product of rainfall intensity is provided every minute with a horizontal resolution of approximately 250 m estimated from the radar reflectivity and specific differential phase shift, KDP as described in Maesaka et al (2011). The accuracy of the XRAIN rainfall was verified by comparison with surface observations (Tsuchiya et al 2015). Japan Meteorological Agency mesoscale analysis data (JMA-MA, JMA 2013) were also used to examine the environmental situation.…”
Section: Observation Data and Processingmentioning
confidence: 99%
“…As for cumulative rainfall volume, although there exists around 20% gap at Kugayama Bridge, they reproduce almost the precise volume. The precision of total rainfall volume is evaluated by the total rainfall ratio (total volume of X-band MP radar data divided by that of ground observation data), which has also been used in existing studies [3] as primary index. Around 10 to 20% gap in the total rainfall ratio is considered acceptable in existing studies.…”
Section: Target Basin and Rainfallmentioning
confidence: 99%
“…The system provides detailed spatial and temporal distribution of rainfall data. The accuracy of X-band MP radar rainfall has been improved through recent studies on the characteristics of observation and precise estimation method of radar rainfall [3][4][5]. Existing studies utilizing the X-band MP radar rainfall with high resolution include: the verification of the preciseness of rainfall or snowfall estimation by ground observation rainfall data [6], comparison of radar data and ground observation rainfall through range analysis in Nagoya region [7], and verification of estimated rainfall volume and spatial accuracy for rainfall events of low temporal resolution [8].…”
Section: Introductionmentioning
confidence: 99%